The Relationship Between Energy Drinks A and B with Blood Pressure and Pulse Rate Increase Among College Students - Setiabudi, Narendra Arya; Pikir, Budi Susetyo; Lestari, Pudji; Purwanto, Bambang (Journal of Community Medicine and Public Health Research, 2024)
Energy drinks are popular among various groups of people, such as teenagers and working individuals. These beverages are consumed to provide additional energy and improve focus. This research investigates the relationship between energy drinks and blood pressure and heart rate in students of the Faculty of Medicine at Universitas Airlangga, Surabaya, Indonesia. The study used the open trial – randomized cross-over study method and collected primary data through experiments. The sample consisted of students from the Faculty of Medicine at Universitas Airlangga, aged 19 to 22 years, with a normal body mass index ranging from 18.5 to 24.9. The systolic, diastolic, and heart rate values were measured before and after consuming energy drinks. A total of 38 research samples were used, including 22 males (57.8%) and 16 females (42.1%). Energy drinks such as Kratingdaeng and Extra Joss showed a significant increase in blood pressure. However, no significant changes were observed in heart rate. The results of the Wilcoxon statistical test, comparing systolic and diastolic conditions before and after consuming Extra Joss, showed p<0.0001. A significance level of p<0.05 indicates a significant effect of energy drinks on the students. The Wilcoxon test for Kratingdaeng also yielded a p<0.0001. For the p-value through the Wilcoxon test on diastolic values before and after consuming Extra Joss and Kratingdaeng, the result was p<0.05. However, the Wilcoxon test for heart rate before and after consuming Kratingdaeng and Extra Joss had a at p<0.05. In the Mann-Whitney statistical test, a p<0.05 was found only in the post-systolic condition, while other conditions had at pâ‰¥0.05. In conclusion, energy drinks significantly affected blood pressure, but no significant changes were observed in heart rate.